Dekonstruksi Narasi Sejarah Perempuan dari Perspektif Kritis Guru Sejarah - Dhita, Aulia Novemy; Nana Supriatna; Didin Saripudin; Erlina Wiyanarti (Universitas Hamzanwadi, 2025)
History education is a strategic instrument for politics and ideological indoctrination. This tendency creates the dominance of the grand narrative in historical education, leading to injustice toward women. Women's representation is often singular and masculine in nature. For instance, Kartini is highly revered, overshadowing the contributions of other women. Historical narratives also frequently prioritize women's involvement as warriors or politicians. This imbalance can be addressed through the role of critical history teachers. This study aims to analyze how history teachers deconstruct women's historical narratives from a critical perspective. The research employs a case study method with a deconstructive approach to women's historical narratives. Data collection is conducted through interviews and documentation. The research subjects are history teachers from Sumatera Selatan Senior High School and Lifeskill Teknologi Informatika Indo Global Mandiri (LTI IGM) Senior High School in Palembang. The research findings indicate that critical history teachers deconstruct Kartini's narrative and offer alternative historical figures. They also critique the dominant narrative that primarily highlights women as warriors or politicians by introducing figures such as Dewi Sartika. Through Dewi Sartika’s Sakola Kautamaan Istri, history teachers emphasize the relevance of the domestic sphere in history. The deconstruction of dominant women's narratives by history teachers fosters a more diverse representation of women's roles in history. Ultimately, this approach contributes to critical and inclusive history education.